СТРАТЕГІЧНИЙ МАРКЕТИНГ В УМОВАХ ВОЄННОЇ НЕСТАБІЛЬНОСТІ: ВИКЛИКИ ТА АДАПТАЦІЙНІ МЕХАНІЗМИ - Pacheva, Nataliia; Korniienko, Tetyana (Zhytomyr Ivan Franko State University, 2025)
The article examines the features of the formation and implementation of strategic marketing in conditions of military instability, which causes radical changes in the functioning of the national economy and market systems. The essence and interrelation of the concepts of "strategic marketing", "military instability", "adaptive mechanisms" and "enterprise competitiveness" are revealed. Attention is focused on the fact that strategic marketing during the war period acts not only as a tool for maintaining market positions, but also as an effective mechanism for adapting business to crisis conditions. The key areas of influence of military factors on the marketing activities of enterprises are identified, in particular, a decrease in effective demand, the destruction of logistics chains, resource shortages and changes in consumer priorities. It is proved that the successful adaptation of enterprises to the conditions of a military environment requires a rethinking of strategic approaches to management, flexibility of marketing decisions and the introduction of innovative models of behavior in the market. The role of the innovative potential of an enterprise as a basis for the formation of competitive advantages in an unstable environment is considered. It is emphasized that strategic marketing management should focus not only on short-term survival, but also on ensuring sustainable development after the end of hostilities. Particular attention is paid to anti-crisis marketing tools, which include diversification of sales channels, development of digital communications, reorientation of target segments and formation of a socially responsible brand image. It is established that strategic marketing in conditions of military instability becomes an integration element of the enterprise management system, which combines analytical, planning, communication and adaptation functions. It is substantiated that the use of a strategic approach to marketing activities allows enterprises to monitor changes in the market environment, increase the flexibility of management decision-making and promptly respond to the challenges of the external environment. It is noted that in modern conditions, innovative activity and strategic thinking become the main factors in increasing competitiveness. The article concludes that strategic marketing in wartime should perform adaptive, stabilizing and prognostic functions aimed at the formation of long-term competitive advantages. The implementation of a systemic approach to marketing management ensures increased stability of the enterprise, reduces risks in the process of its functioning and creates a basis for restoring the country's economic potential. Thus, strategic marketing in conditions of war instability becomes a key factor in maintaining business efficiency, developing innovative activities and ensuring the competitiveness of the national economy as a whole.